Effective Bible teaching - Wilhoit, Jim.; Ryken, Leland (Grand Rapids, MI : Baker Academic, 2012)
"Why does Bible study flourish in some churches and small groups and not in others? In this updated edition of a trusted classic, two Christian education specialists provide readers with the knowledge and methods needed to effectively communicate the message of the Bible. The book offers concrete guidance for mastering a biblical text, interpreting it, and applying its relevance to life. Its methods, which have been field-tested for twenty-five years, help pastors, teachers, and ministry students improve their classroom skills. Readers will learn how to develop the "big idea" of a passage and allow the text itself to suggest creative teaching methods. This new edition has been updated throughout and explores the changed landscape of Bible study over the past two decades. Readable and interdisciplinary in approach, this book will help a new generation of Bible students teach in a purposeful and unified way"--Publisher description.
Part 1. Effective teaching. The changing landscape of Bible study -- The church's unfinished task -- The tasks of the effective teacher -- The teacher : the human element in teaching -- Part 2. The methods of effective Bible teaching. Discovering unity in biblical passages : the genre and structure of a passage -- Thematic unity in biblical passages : teaching the big idea -- Bridging the gap -- Principles of biblical interpretation -- Understanding the methods of inductive and directed Bible studies -- Leading inductive Bible studies -- Part 3. The Bible we teach. What kind of book is the Bible? -- Types of writing in the Bible -- Teaching the stories of the Bible -- Teaching the poetry of the Bible -- Teaching other genres of the Bible.
Includes bibliographical references and indexes.
Keywords: Bible -- Study and teaching